Sources Reliability Evaluation: the Beginning of the News Quality - Nakwanit, Rattanawadee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This article studies how reporters evaluate the credibility of news sources, drawn from information gathered from literature and interviews with political beat reporters. The study showed that reliability is the most important factor in the selection of news sources. Reporters' observation is the most credible source, followed by documentary Source and human source respectively. Four dimensions on which reporters based their evaluation of human source's credibility were trustworthiness ,appearance, motivation and status- position. The guidelines to evaluate the credibility of news sources are described by the news source as follows 1. To determine whether the sources were reliable, reporters asked themselves about how this person knew this information, whether the record of this source was reliable, whether this source had any bias or confict of interest that would compromise the integrity of what he/ she said, whether this information was available from other sources and could be verified. 2. To determine whether documentary source was reliable ,reporter was to rely on primary documentary source rather than secondary documentary source . 3. To determine whether online sources were reliable, reporter used crowd sourcing and cross-referencing to verify social media sources. The study also found that reporters rated sources in different level based on their intuition as a part of the process of deciding whether sources were reliable. Reporters must report quickly, although the process could not be done within a short time. Under such restrictions, reporters tried to avoid the use of the political overtones language.